2013
DOI: 10.1111/cei.12022
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentration of immunoglobulin G-type antibodies against the whole Epstein–Barr nuclear antigen 1 and its aa35–58 or aa398–404 fragments in the sera of patients with systemic lupus erythematosus and multiple sclerosis

Abstract: SummarySeveral studies suggest that infection by Epstein-Barr virus (EBV) might be one of the environmental factors which facilitates the development of autoimmune disorders in genetically susceptible individuals. Recent data indicate that high anti-Epstein-Barr nuclear antigen 1 (EBNA)-1 immunoglobulin (Ig)G titre is a strong risk factor for multiple sclerosis (MS) in patients both with and without the main genetic predisposing trait, human leucocyte antigen (HLA)-DRB1*15:01. Because no similar studies have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Studies have shown an increased number of latently EBV-infected cells [ 18 ] and an abnormally high viral load in the peripheral blood mononuclear cells of SLE patients [ 19 21 ]. Also, an impaired EBV-specific T cell response is observed in SLE patients [ 19 , 30 32 ] and an increased serologic response has been demonstrated with high titers of antibodies to EBV antigens in SLE patients compared to healthy controls [ 29 , 33 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown an increased number of latently EBV-infected cells [ 18 ] and an abnormally high viral load in the peripheral blood mononuclear cells of SLE patients [ 19 21 ]. Also, an impaired EBV-specific T cell response is observed in SLE patients [ 19 , 30 32 ] and an increased serologic response has been demonstrated with high titers of antibodies to EBV antigens in SLE patients compared to healthy controls [ 29 , 33 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, linear epitope mapping studies found serum IgG binding to EBNA1 398 -411 also in patients with systemic lupus erythematosus (SLE) (94) and in patients with infectious mononucleosis (a disease resulting from primary infection with EBV) (95) at elevated levels in comparison to healthy controls. The region was shown to cross-react with the sequence "PPPGMRPP" of the lupus spliceosomal autoantigen SNRPB (95,96). Moreover, as described above, the region contains the sequence motif "RRPFF" (EBNA1 402-406), which is also present in CRYAB (84).…”
Section: Cryab: Igg Binding the N-terminal Region Maymentioning
confidence: 84%
“…Otherwise, in line with previous studies (88,90), serum IgG to EBNA1 52-100 were significantly more frequently observed in the MS group (Table II). A study with nasopharyngeal carcinoma (NPC) patients, however, also showed increased IgG and IgA reactivities to this region in comparison to healthy subjects (97), and antibodies to an epitope overlapping with this region (EBNA1 were found at higher concentrations in sera of both SLE and MS patients (96). Thus, EBNA1 52-100 harbors distinct epitopes, which explains the differences between the individual patients in the data for the four filtered peptides (see "Results").…”
Section: Cryab: Igg Binding the N-terminal Region Maymentioning
confidence: 99%
“…7-9 24 Furthermore, a serologic connection between EBV and SLE has been demonstrated by increased titres of antibodies to EBV antigens in SLE patients compared with healthy controls (HCs). 23 [25][26][27][28][29][30][31][32][33][34][35][36][37] Previous studies on EBV-specific T-cells are in discordance. Three individual studies have shown that SLE patients have fewer cytotoxic CD8 T-cells with a decrease in effector responses upon stimulation with EBV.…”
Section: Introductionmentioning
confidence: 99%